KOORDINASI PENERTIBAN RUMAH PENAMPUNGAN IMIGRASI KOTA PEKANBARU TAHUN 2020-2024 - Aszri, Sholihin; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Republic of Indonesia, which consists of islands and its abundance of natural wealth, is an attraction for foreign citizens seeking asylum and choosing to settle in one of the regions of Indonesia. The large number of foreigners who come to Indonesia for vacation and there are also those who stay but do not have an official permit to stay in Indonesia, the increasing number of immigrants entering the Pekanbaru City area has resulted in the capacity of one of the immigration shelters, namely the Satria shelter, being full. So, institutional coordination is needed regarding the excess capacity of Pekanbaru City immigration shelters in 2020. This research uses a qualitative research method with descriptive data analysis. In collecting data, researchers used interview, observation and documentation techniques. The results of this research can be seen that coordination between Pekanbaru City National Unity and Politics and the Immigration Detention Center is related to the excess capacity of the Pekanbaru City immigration detention center in 2020 due to a lack of coordination between the two institutions which can hamper the work of both parties, the weak quality of personnel capabilities, and lack of depth regarding the applicable legal basis. Keywords: Coordination, Shelter House, Excess Capacity